A content analysis of khutbah Jumaat / Ahmad Ibrahim - Ibrahim, Ahmad (2002)
Khutbah Jumaat or Islamic sermon is one of the integral elements in Islam. It is delivered before Salat Juma'at. The objective of the khutbah is to preach and remind Muslims to practice the Islamic teachings. This study is conducted to find a relevant pattern and trend used in the khutbah of JAIS (Jabatan Agama Islam Selangor) and Masjid Negara. 214 khutbahs of both institutions are analyzed in terms of verses used, types, length, and styles of writing of the khutbahs. The findings show that • Both institutions are responsive to feedbacks from the public, current issues and the need of the society. • The length of khutbah has improved to suit the constraints of time and condition. The presentation of khutbah will be more effective if the khatib uses the latest technologies, the khutbah should be brief, simple and well prepared. This study is aimed at improving the quality of khutbah for the future.